2015
DOI: 10.1038/ncomms9246
|View full text |Cite
|
Sign up to set email alerts
|

An insight into non-emissive excited states in conjugated polymers

Abstract: Conjugated polymers in the solid state usually exhibit low fluorescence quantum yields, which limit their applications in many areas such as light-emitting diodes. Despite considerable research efforts, the underlying mechanism still remains controversial and elusive. Here, the nature and properties of excited states in the archetypal polythiophene are investigated via aggregates suspended in solvents with different dielectric constants (ɛ). In relatively polar solvents (ɛ>∼ 3), the aggregates exhibit a low fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
64
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(75 citation statements)
references
References 66 publications
(102 reference statements)
7
64
0
3
Order By: Relevance
“…Hu et al observed that long-range exciton transport depends strongly on aggregate order [26], further highlighting the importance of interchain interactions on exciton dynamics. In a further study, Hu et al demonstrated that dielectric-induced stabilization of nonradiative charge-transfer states very sensitively controls PL quantum efficiencies in suspended P3HT aggregates [27], consistent with the role proposed by Yamagata et al of charge-transfer components of excitonic coupling [25], indicating once again the key role the environment plays in dictating photophysics in aggregates.…”
Section: -3supporting
confidence: 56%
“…Hu et al observed that long-range exciton transport depends strongly on aggregate order [26], further highlighting the importance of interchain interactions on exciton dynamics. In a further study, Hu et al demonstrated that dielectric-induced stabilization of nonradiative charge-transfer states very sensitively controls PL quantum efficiencies in suspended P3HT aggregates [27], consistent with the role proposed by Yamagata et al of charge-transfer components of excitonic coupling [25], indicating once again the key role the environment plays in dictating photophysics in aggregates.…”
Section: -3supporting
confidence: 56%
“…The photoexcitation will also occur at the polymer crystalline phase and conduct the efficient exciton-diffusion. Such exciton may not contribute to the highly stable interchain CT generation because of the lack of the electronic stabilizations [5] in the CT character at the crystalline phase in Fig. 4, resulting in dominant radiative deactivations by the fluorescence.…”
Section: Resultsmentioning
confidence: 99%
“…Such crystalline phases are known to play a key role for the mobilities of the charges and the excitons in the organic devices. Recent studies suggested that non-fluorescent CT characters exist as a competitive channel of the formation of emissive exciton-type states and determine the light emission efficiencies of the LED films [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3(b). O líquido escolhido para realizar este experimento foi o hexano (marca ISOFAR), cuja constante dielétrica estática é bem determinada na literatura [7] e o grau de pureza é industrialmente garantido (98,5%). Aqui é importante ressaltar que a água não foi utilizada como meio dielétrico, pois os experimentos realizados com esta indicam que mesmo água filtrada possui alto grau de impurezas químicas uma vez que a mesma é previamente tratada pelo sistema de abastecimento.…”
Section: Materiais E Métodosunclassified